Relationship between self-regulated learning, social media usage and motivation among Arabic learners in Malaysian public universities / Di Xuan - Di , Xuan (2020)
This study aimed at investigating the relationship between self-regulated learning strategies, social media usage, and motivation, as well as the influences of three variables to Arabic learners' Academic achievement (GPA) in Malaysian public universities. To collect the data, a number of 317 male and female undergraduate Malaysian Arabic learners were randomly selected from six public universities in Malaysia as participants of this study. The instruments were developed from Jansen et al., (2017), Monachesi et al., (2008), and Pintrich et al., (1991). Then, IBM SPSS was used for data screening and descriptive analysis whereas Smart-PLS were applied to analysis most of the inferential statistics and develop models for the influence of self-regulated learning strategies, social media usage and motivation on academic achievement, as well as the mediation effect among three variables. The findings indicated Arabic learners with medium level self-regulated learning strategies, social media usage and high level of motivation in Arabic learning. Moreover, the participants frequently use metacognitive skill and help-seeking strategies but rarely use time management in learning. Additionally, the degree of self-regulated learning strategies, social media usage, and motivation are not significantly different in gender and year of study. The result further revealed that learners' self-regulated learning strategies, social media usage, and motivation significantly correlation each other, and there is a significant effect of Arabic learners' self-regulated learning strategies on academic achievement. Meanwhile, there is no significant effect of motivation and social media usage on learners’ academic achievement. Besides, the finding of this study also indicated self-regulated learning strategies are a significant mediator of the relationship between motivation and social media usage among Arabic learners. The findings of this study provided fresh empirical evidence to support with the social cognitive theory that there is a statistically significant positive correlation between self-regulated learning strategies, social media usage and motivation in Arabic learning context in Malaysian public universities. On the other hand, this study also presented the procedures of Arabic learners using social media to support self-regulated learning in Arabic learning. This contribution finding unfolds new understandings regarding the Arabic language as second language pedagogy in Malaysia. Consequently, this study have provide several theoretical and practical implications, practicing the procedures of Arabic learners' using social media to support self-regulated learning in Arabic learning and metacognitive skills, help-seeking strategies deem to be considered crucial in Arabic learning.